Maria C. Shaw and Anne P. Chapin (with contributions by E.W. Barber, G. Bianco, B. Burke, E. C. Egan and S. Peterson Murray). Woven Threads. Patterned textiles of the Aegean Bronze Age (Ancient Textile Series 22). - Sarri, Kalliope (Journal of Greek Archaeology, 2018)
Aegean studies and textile research welcome a new book with an original and highly specialized topic. Contrary to previous research that was orientated more to weaving technologies, this volume is devoted to textile design and connects fabric technologies with different expressions of the visual arts. The book focuses first and foremost on a detailed analysis of patterns and in this way it upgrades patterning from a simple decorative medium to an important key for understanding the applied thread technologies, the evolution of design and a series of craft transfers during the Late Bronze Age. Furthermore, it postulates a new research area supplying evidence for intercultural relations between people of the Aegean and the East Mediterranean.